Evidence-Informed Development of a Bundle for Peripheral Intravenous Catheterization in Portugal: A Delphi Consensus Study - Paulo Santos-Costa; Filipe Paiva-Santos; Liliana B. Sousa; Rafael A. Bernardes; Filipa Ventura; Anabela Salgueiro-Oliveira; Pedro Parreira; Margarida Vieira; João Graveto (MDPI AG, 2022)
Contrary to many international settings, there are no clinical guidelines for peripheral intravenous catheter (PIVC) insertion and maintenance in Portugal. We sought to derive an international consensus on a PIVC bundle that could guide Portuguese nurses' clinical decision-making in this scope. Methods: Two international vascular access specialist groups participated in an online Delphi panel. During the first round, specialists (n = 7) were sent a summary report from a previous observational study conducted in a surgical ward in Portugal. Based on the report findings, specialists were asked to provide five to eight PIVC insertion and maintenance interventions. Then, another set of specialists (n = 7) scored and revised the recommendations until a consensus was reached (≥70% agreement). The PIVC bundle was made available and discussed with the surgical ward's nurses. Results: After three rounds, a consensus was achieved for five evidence-informed interventions: (i) involve the person and assess the peripheral venous network; (ii) maintain an aseptic no-touch technique; (iii) ensure proper catheter dressing and fixation; (iv) perform catheter flush & lock; (v) test the peripheral venous catheter's functionality and performance at each shift. Conclusion: The final version of the PIVC bundle achieved consensus among international experts. Despite the positive feedback provided by the ward nurses, future studies are warranted to assess its effectiveness in standardizing PIVC care delivery and its potential implications for care outcomes in Portuguese clinical settings.